Financial development and countries' production efficiency: A nonparametric analysis - Nickolaos G. Tzeremes (Journal of Risk and Financial Management, 2018)
This paper examines the effect of financial development on countries' production efficiency levels. By applying a probabilistic framework it develops robust (Order-m) time-dependent conditional nonparametric frontier estimators in order to measure 87 countries' production efficiency levels over the period 1970-2014. In order to examine the effect of time and domestic credit on countries' production efficiency levels, a second-stage nonparametric econometric analysis is performed. Specifically, generalized additive models with tensor products and cubic spline penalties are applied in order to investigate the potential nonlinear behavior of financial development on countries' production efficiency levels. The results reveal that the effect of financial development on production efficiency is nonlinear. Specifically, the effect is positive up to a certain credit level after which it becomes negative. Finally, the evidence suggests that the effect is influenced by a country's financial system, institutional, and development characteristics.
Keywords: 330; financial development; production efficiency; nonparametric frontiers; generalized additive models; tensor products; cubic spline penalty